Florianopolis city football clubs: sociodemographic and behavioral profile - Silva, Walan Robert (2017)
The aim of study was to verify the sociodemographic and behavioral profiles of the football stadium goers, associated or not, to their teams and groups of football fans. A questionnaire was applied that measured the socioedemographic profile and behavior of football fans. Participated in this study 638 people with an average age of 29.5 ± 12.4 years; 69.6% male and 30.4% female. The results showed that the older fans generally have better financial conditions. Organized fans, followed by the associate's supporters have greater bond with the club, and they are the ones who consume more products related to their clubs. Still, the organized fans were the group that showed angry after a defeat of their clubs. Thus, we conclude that the greater the fan connection with the club, the greater are their costs with the same, besides a larger amount of emotions and intensity linked to clubs performances.